2014
DOI: 10.1364/ome.4.000396
|View full text |Cite
|
Sign up to set email alerts
|

Versatile luminescence of Eu^2+,3+-activated fluorosilicate apatites M_2Y_3[SiO_4]_3F (M = Sr, Ba) suitable for white light emitting diodes

Abstract: Eu-doped fluorosilicate apatites M 2 Y 3 [SiO 4 ] 3 F (M = Sr, Ba) are prepared by solid state reaction. Unlike conventional Eu-doped materials, coexistence of Eu 3+ and Eu 2+ ions is found from the photoluminescence of Eu-doped apatites M 2 Y 3 [SiO 4 ] 3 F (M = Sr, Ba) which were prepared in reducing atmosphere. Eu 2+ ions are converted from Eu 3+ ions in the reduction process. It is suggested that Eu 2+ ions occupy A(I) (4f) or A(II) (6h) crystallographic site in the apatite lattices. Intense emission lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…It can be observed that all of the excitation spectra have the same profile in addition to the intensity. Qi et al [29] prepared Eu 3 þ -doped Ba 2 Y 3 (SiO 4 ) 3 F and found the charge transfer band (CTB) of Eu-O at 255 nm. Blasse and Brill [35] found that the CTB energy of Sm 3 þ in compounds always appears 1.170.1 eV higher than that of Eu 3 þ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that all of the excitation spectra have the same profile in addition to the intensity. Qi et al [29] prepared Eu 3 þ -doped Ba 2 Y 3 (SiO 4 ) 3 F and found the charge transfer band (CTB) of Eu-O at 255 nm. Blasse and Brill [35] found that the CTB energy of Sm 3 þ in compounds always appears 1.170.1 eV higher than that of Eu 3 þ .…”
Section: Resultsmentioning
confidence: 99%
“…With the increase in Ce 3 þ doping concentration, the maximum emission wavelength from to the 5d to 4f transition on Ce 3 þ ions in Ba 2 Y 3À x Ce x (SiO 4 ) 3 F shows a redshift from 405 nm (x¼ 0.005) to 460 nm (x¼ 0.07). Huang et al reported the two kinds of luminescence centers give a broad band in a spectral range from blue to red in Ba 2 Y 3 (SiO 4 ) 3 F:Eu 3 þ ,Eu 2 þ phosphors [29]. However, to our knowledge, there has been no report on the luminescence properties of Sm 3 þ -doped Ba 2 Y 3 (SiO 4 ) 3 F apatite phosphor.…”
Section: Introductionmentioning
confidence: 97%
“…A broad peak centred at 496 nm and 514 nm corresponding to the transition 4f 6 5d 1 -4f 7 has been observed corresponding to Eu 2+ . [53][54][55] As the amount of Eu doping was very miniscule, the doping amount was increased to 2.5% to obtain a relatively higher intensity of emission. Furthermore, relatively weaker peaks at 595 nm, 616 nm, 653 nm and 703 nm, characteristic of Eu 3+ , were also observed in the photoluminescence spectra of the materials.…”
Section: Surface Area Analysismentioning
confidence: 99%
“…Rare earth element (REE) containing silicates are one class of inorganic metal oxide-based phosphors that have been intensively studied for these purposes. Examples include garnets such as Ca 3 Sc 2 Si 3 O 12 :REE 3+ [2][3][4], the group of M 2 SiO 4 : REE 3+ (M:Ca, Sr, Ba) compounds [5][6][7] or apatites such as Ca 2 Gd 8 -(SiO 4 ) 6 O 2 :Er 3+ , Ca 4 Y 6 (SiO 4 ) 6 O:Eu 3+ and M 4 Y 6 [SiO 4 ] 6 F 2 :Eu 2+,3+ (M: Sr, Ba) [8][9][10]. Another promising silicate material that allowed a wide-range tuning of the optical properties from blue emitters and IR S-band amplifiers to X-ray phosphors depending on the type and the content of the REE cation was reported by Ananias et al [11]: Na 3 (Y 1-x M x )Si 3 O 9 (M:Tm 3+ , Tb 3+ ; x = 0-1).…”
Section: Introductionmentioning
confidence: 99%